Disc versus wind accretion in X-ray pulsar GX 301-2. Issue 2 (5th April 2021) - Liu, Jiren; Ji, Long; Jenke, Peter A; Doroshenko, Victor; Liao, Zhenxuan; Li, Xiaobo; Zhang, Shuangnan; Orlandini, Mauro; Ge, Mingyu; Zhang, Shu; Santangelo, Andrea
ABSTRACT: GX 301-2 provides a rare opportunity to study both disc and wind accretion in a same target. We report Insight - Hard X-ray Modulation Telescope observations of the spin-up event of GX 301-2 that happened in 2019 and compare with those of wind-fed state. The pulse profiles of the initial rapid spin-up period are dominated by one main peak, while those of the later slow spin-up period are composed of two similar peaks, as those of wind-fed state. These behaviours are confirmed by Fermi /Gamma-ray Burst Monitor data, which also show that during the rapid spin-up period, the main peak increases with luminosity up to 8 × 10 37 erg s −1, but the faint peak remains almost constant. The absorption column densities during the spin-up period are ∼1.5 × 10 23  cm −2, much less than those of wind-fed state at similar luminosity (∼9 × 10 23  cm −2 ), supporting the scenario that most of material is condensed into a disc during the spin-up period. We discuss possible differences between disc and wind accretion that may explain the observed different trends of pulse profiles.